Differences in functional properties of mungbean protein concentrate and the effect of incorporation into fish sausages - Mohamed, Suhaila; Bakar, Jamilah; Abd. Hamid, Norhashimah (Universiti Putra Malaysia Press, 1996)
The physico-chemical and functional properties of mungbean protein concentrate prepared by (i) calcium sulphate precipitation (MBC-Ca) and (ii) isoelectric point precipitation (MBG-pI) containing 21.6 and 67.3% protein respectively, were compared. The solubility of the concentrates was positively correlated with pH within the range of 4-7. The foaming ability was closely correlated with percentage ofsoluble N (r2 = 0.98) and pH (r2 = 0.88) while the foam stability was correlated with the hydrophilicity (l = 0.98) of the concentrates. All concentrates were able to reduce the weight loss, shrinkage and increase the firmness of cooked fish sausages. The weight loss and shrinkage were negatively correlated with the soluble protein, pH and foaming ability of the concentrates. The functional properties of the concentrates, when added at a level of 1-2%, influenced the texture of the fish sausages. In organoleptic evaluations, fish sausages incorporating the plant proteins scored higher for overall acceptability, even though there was no significant difference in flavour or texture and a decrease in juiciness of the product compared to the control.